Nursing care process in a adolescent with interruption of family processes according to taxonomy NANDA-NIC-NOC: Proceso de cuidado de enfermería en adolescente con interrupción de procesos familiares según taxonomía NANDA-NIC-NOC - Goyzueta, Ana Paula (2019)
The nursing care process, allows to know the experiences and situations of the family. This paper describes the assessment, analysis and interpretation of the situation of a teenager diagnosed with interruption of family processes and subsequent planning, intervention and evaluation. In the hospital and community field, it is recommended to use the NANDA NIC-NOC taxonomy, because it allows us to understand the problem holistically, from the individual, family and social environment. Keywords: Home Health Nursing, Nursing Care; Adolescent (Source: MeSH, NLM).